“Buried Alive”: Experience, Memory, and the Interwar Publishing of the Egyptian Expeditionary Force in Postwar Britain, 1915-1939 - Fantauzzo, Justin (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2012)
Over 450,000 British soldiers fought as part of the Egyptian Expeditionary Force during the First World War. Between 1915-1918, they fought their way across the Sinai Peninsula, into southern Palestine, captured Jerusalem, and overran the Turkish Army, leading to the surrender of the Ottoman Empire in October 1918. Despite being the war’s most successful sideshow, the Egypt and Palestine campaign struggled to gain popular attention and has largely been excluded from First World War scholarship. This article argues that returning soldiers used war books to rehabilitate the campaign’s public profile and to renegotiate the meaning of wartime service in interwar Britain. The result of sporadic press attention and censorship during the war, the British public’s understanding of the campaign was poor. Periodic access to home front news meant that most soldiers likely learnt of their absence from Britain’s war narrative during the war years. Confronting the belief that the campaign, prior to the capture of Jerusalem, was an inactive theatre of war, British soldiers refashioned themselves as military labourers, paving the road to Jerusalem and building the British war machine. As offensive action intensified, soldiers could look to the past to provide meaning to the present. Allusions to the campaign as a crusade were frequently made and used to compete with the moral righteousness of the liberation of Belgium.